Upstream technical efficiency and its determinants: Evidence from non-parametric and parametric analysis of Nigeria exploration and production (E & P). Issue 1 (1st January 2019) - Adekunle, Idowu J.; Omowumi, Iledare O.; Joseph, Echendu C.; Peter, Achi O.
Abstract: The study empirically estimates the relative technical efficiency of Nigeria upstream petroleum industries and its determinants using non-parametric and parametric analysis. The non-parametric analysis' results reveal that joint venture contract operators, marginal field contract operators, sole risk contract operators, production sharing contract operators, service contract operator and national oil company contract have the following technical efficiency grades: 75%, 67%, 65%, 64%, 42% and 23%, respectively. On the other hand, the parametric analysis result indicates that four of the selected independent variables are statistically significant determinants of the upstream technical performance. The findings support the plan exit of cash calls policy by the government and confirm that the proposed exit of the model is not harmful to both the government and the investors. For the indigenous participants, we submit that the government may put in place attractive incentives policy to encourage more indigenous participation in the upstream business.